Effect of alkali on tropical peat stabilized with different stabilizers - P.K, Kolay; M.R, Aminur; S.N.L., Taib (Universiti Malaysia Sarawak, 2011)
The paper presents the effect of alkali on tropical peat stabilized with ordinary portland cement (OPC), fly ash (FA) and different chemicals e.g., accelerator (a combination of 2.0% sodium sulfate, 0.5% sodium chloride and 0.1% triethanolamine); 2.6% aluminum sulfate; and 2.6% calcium sulfate. Various physical and engineering properties tests were conducted on original peat, FA and stabilized peat samples to check the effect of alkali and chemicals. Unconfined Compressive Strength (UCS) tests were carried out on treated (i.e., peat treated with 2% NaOH to reduce its acidity) and untreated stabilized peat samples with OPC, FA, and different chemicals for various curing periods. The results show that UCS value increases with curing periods and treated peat samples show better results than untreated peat for both OPC and FA stabilized peat samples. The highest UCS value was found on treated stabilized peat where calcium sulfate and OPC were used as stabilizers for 120 days curing period. In addition, specific gravity (Gs), pH, loss on ignition (N), Organic Content (OC) and Scanning Electron Microscope (SEM) studies were also carried out on stabilized peat samples to investigate the stabilized behavior and micro-structure of the peat.